(untitled) (Journal of Dhaka Medical College, 2024)
Cardiac manifestations are occasionally observed in Systemic Sclerosis patients. Primary cardiac involvement may occur as a direct consequence of the disease. Arrhythmias are also thought to be a direct result from conduction system fibrosis. Early diagnosis and treatment of arrhythmia can be rewarding for this patient as if intreated may lead to a fatal outcome. Beta blockers used to treat arrythmia may worsen Raynaud’s symptom in systemic sclerosis. So there has been a controversy regarding the treatment of arrhythmia in Systemic Sclerosis. Here we are reporting a case of Systemic Sclerosis who presented with palpitation and digital gangrene. Her resting ECG showed multiple premature ventricular complexes whereas echocardiogram did not show any significant abnormality. Then She was treated with non-selective beta blocker without any progression of her Raynaud’s. For her digital gangrene, along with other conventional treatment (like nifedipine & tadalafil) she was treated with endothelin receptor antagonist (bosentan) and showed good response. J Dhaka Med Coll. 2023; 32(1) : 92-95